A comparison approach for accuracy feature of requirements prioritization models - Jenjira Jaimunk (2018)
© Springer-Verlag Berlin Heidelberg 2015. As the quality of software defined by the users satisfaction, in order to maximize the users satisfaction under constrains of budget, time and resource, the software engineer need to prioritize the requirements. Requirement prioritization involves identifying the core requirements used for project planning. This article proposes a method to compare the accuracy of requirement prioritization model. The subjects include customers, project leaders, users and the representatives of developer such as programmers and testers. They have to select a related list of requirements among two sets of requirements. Those pair lists of requirements have to be the same order from difference prioritizing models. Whereas, the subjects don't realize those which requirements are belong to which practical model. The main objective of this study is to assess the accuracy of a proposed model with a reference model. The results show that the proposed approach provides precise measurement of accuracy for prioritizing model.